Formulation Design and in-Vitro Evaluation of Simvastatin Pulsatile Drug Delivery System - Srikanth (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Theaimofthestudy wasto prepare Simvastatin pulsatile tablets to release the drug at predetermined time after a lag period, so that drug from the formulation will be released according physiological need of the body for the effective treatment of peptic ulcer .The approach of the present study was to make a comparative evaluation among concentration of these polymers and to assess the effect of physico-chemical nature of the active ingredients on the drug release profile. The ? max of Simvastatin in 7.2 pH Phosphate buffer was scanned and found to have the maximum absorbance at 247 nm. Standard graph of Simvastatin in 7.2 pH phosphate buffer was plotted. The Bulk density and tapped density of the Controlled release tablets were found to be 0.39-0.56 and 0.44 to 0.69 respectively. The angle of repose values obtained for the Controlled release tablets ranged from 18.17 to 25.98 This indicates good flow property of the powder blend. The compressibility index values for the Simvastatin Pulsatile tablets ranged from 12.24 to 20.0 This indicates the powder blend have good flow property. The cars index values for the Simvastatin Pulsatile tablets ranged from 1.057 to 1.26 This indicates the powder blend have good flow property. In vitro drug release profiles for all Simvastatin Pulsatile tablets were carried out by using 7.2 pH phosphate buffer as dissolution medium for about 24 hrs. From the above results it was found that the release of drug from F12 formulation with Eudragit RLPO gave the better release than other Simvastatin Pulsatile tablets.